Performance of Quail with Different Hatch Body Weight by Fasting Treatment Post-hatch - Bahri Syamsuryadi; K. Khaeruddin (Chalaza Journal of Animal Husbandry, 2018)
The purpose of this study was to determine the relationship of broiler quail’s initial body weight which is fastened at post-hatch to growth and attainment the last body weight. One hundred thirty-five quails aged 12 post-hatch had kept in a cage plot which had prepared based on a completely randomized design with 3x3 factorial pattern and three replications which each replication consisted of 5 quails. The first factor is body weight post-hatch (B) consist of B1 = 5.1 – 6.0 g (light), B2 = 6.1 – 7.0 g (medium) and B3 = 7.1 – 8.0 g (heavy), the second factor is the duration of fasting post-hatch (P) consist of P1 = 24 hours, P2 = 36 hours and P3 = 48 hours. The observed parameters to fasting were feed consumption, body weight, and feed conversion. The result of this study is the quail with light early body weight (5.1-6 g) post hatch showed that the lightest last body weight is related to the value of feed conversion. Accession good performance of quail can be reached by access feed approximately 24 hours.